2012
DOI: 10.1523/jneurosci.1451-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease: Presenilin 2-Sparing γ-Secretase Inhibition Is a Tolerable Aβ Peptide-Lowering Strategy

Abstract: ␥-Secretase inhibition represents a major therapeutic strategy for lowering amyloid ␤ (A␤) peptide production in Alzheimer's disease (AD).Progress toward clinical use of ␥-secretase inhibitors has, however, been hampered due to mechanism-based adverse events, primarily related to impairment of Notch signaling. The ␥-secretase inhibitor MRK-560 represents an exception as it is largely tolerable in vivo despite displaying only a small selectivity between A␤ production and Notch signaling in vitro. In exploring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…Bioanalysis of plasma and brain homogenate samples was performed as previously described (Borgegård et al . ). Briefly, the right brain hemisphere was homogenized in two volumes (w/v) of Ringer solution using a multi‐element sonication probe.…”
Section: Methodsmentioning
confidence: 97%
“…Bioanalysis of plasma and brain homogenate samples was performed as previously described (Borgegård et al . ). Briefly, the right brain hemisphere was homogenized in two volumes (w/v) of Ringer solution using a multi‐element sonication probe.…”
Section: Methodsmentioning
confidence: 97%
“…Zhao and colleagues have shown that sulfonamide based GSIs selectively inhibit PSEN1 over PSEN2, whereas the GSIs DAPT and L685458 showed minimal selectivity [105]. Similarly, recent data suggest that the GSI MRK-560 preferentially targets PSEN1 over PSEN2 and that this selectivity, at least in mice, increases the tolerability of this GSI [106]. De Strooper and colleagues also show that heterogeneity with respect to the Aph1 subunit is important with respect to viability and overall phenotype of mice, indicating that selective targeting of Aph1b γ-secretase complexes may be less toxic [107]; however, it is not clear whether selective targeting of Aph1b γ-secretase complexes is feasible.…”
Section: Gsismentioning
confidence: 99%
“…But, interestingly, PSEN2 containing ␥-secretase complexes appear to carry out an important part of the physiological processing of Notch in peripheral organs. The differential activity profiles of PSEN1/2 complexes were actually exploited in a study conducted by Borgegård et al (30) in which in vivo inhibition of APP processing by a PSEN2-sparing ␥-secretase inhibitor (MRK-560) circumvented to a large extent Notch-related side effects. These results demonstrate that PSEN1 and PSEN2 ␥-secretase complexes can be targeted specifically and provide the first preclinical proof of concept that differential targeting of ␥-secretase complexes is a worthwhile strategy in therapy development for AD.…”
mentioning
confidence: 99%